USM SCHOOL OF BIOLOGICAL SCIENCES RECEIVES VISIT FROM PSU THAILAND STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 – 32 students together with 2 lecturers from the Prince of Songkhla University (PSU) Hat Yai, Thailand who specialised in the field of Biotechnology (Molecular Biotechnology and Bioinformatics) visited the School of Biological Sciences (PPSK) Universiti Sains Malaysia (USM) recently, as a followup programme to a prior collaboration between the two institutions.